Banking System Restructuring in Kazakhstan - Hoelscher, David (IMF Working Papers; Working Paper, 1998)
This paper reviews financial restructuring in Kazakhstan, and the condition of the financial system in the period following independence. The authorities' efforts to redress financial sector weaknesses fall into two phases: The first phase addressed the immediate crises in the banking system by slowing bank licensing, tightening prudential regulations, and dealing with large nonperforming loans. The next phase saw reforms to regulatory and institutional structures. The paper shows that, by the end of 1997, substantial reforms in the structure of the financial system had been accomplished and a major financial collapse avoided. However, the banking system had not begun to play an active role in financial intermediation.